Does the market understand the ex ante risk of expropriation by controlling shareholders? - Cheung, Yan-Leung; Rau, P. Raghavendra; Stouraitis, Aris; Tan, Weiqiang (Journal of Corporate Finance, 2021)
We examine how the market values operating assets in the presence of time-varying ex ante risk that these assets may be tunneled away. We analyze pairs of Chinese publicly listed firms and their non-listed parents and examine the market valuation of current assets (cash balances, trade receivables, receivables due from the controlling shareholders, inventories) and fixed assets on the publicly listed firm's balance sheet. Our results show that in periods when the risk of tunneling from the publicly listed firm to its controlling shareholder increases, operating assets that are easy to tunnel (cash and receivables due from the controlling shareholder) are valued at larger discounts, while operating assets that are not easy to tunnel (trade receivables, inventories, fixed assets) are not valued at such discounts.